The ethics of John: Retrospect and prospects - Watt, Jan Gabriël van der; Dulk, Matthijs den (Biblical interpretation series, 2025)
What does John have to offer in terms of ethical content? In this volume, leading experts evaluate Jan van der Watt's recent major contributions to this question and explore future prospects for the study of Johannine ethics.